2019
DOI: 10.1108/ijqrm-11-2017-0245
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management and organizational performance: the resonant influence

Abstract: Purpose A single supply chain management (SCM) practice will have a certain impact on organizational performance (OP). However, since it is placed in a system that many other practices are conducted simultaneously, the practice itself will interact with other ones (i.e. affect/be affected). As a consequence, the efficiency of the affected practice is increased and it is expected to maximize the impact of SCM practices on OP. This mechanism is named the “resonant” influence that is a new approach in the SCM lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
4
16
0
Order By: Relevance
“…The findings of this study support previous research by Althaqafi, (2020) that there is a strong relationship between SCM and operational performance and it impacts each other widely. Furthermore, this finding is in line with the research of (Phan et al, 2019;Duong et al, 2019) which revealed that maintaining supply chain management in the company has a good impact on operational performance. The findings of Vencataya et al, (2016) reinforce the findings of this study that effective SCM practices can have a good effect on operational performance in the company.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study support previous research by Althaqafi, (2020) that there is a strong relationship between SCM and operational performance and it impacts each other widely. Furthermore, this finding is in line with the research of (Phan et al, 2019;Duong et al, 2019) which revealed that maintaining supply chain management in the company has a good impact on operational performance. The findings of Vencataya et al, (2016) reinforce the findings of this study that effective SCM practices can have a good effect on operational performance in the company.…”
Section: Discussionsupporting
confidence: 88%
“…see Quang et al, 2016;Truong et al, 2017). But, these studies viewed SCM practices as independent variables -thus focusing mainly on their direct effects (Duong et al, 2019). The divergence perspectives on SCM practices and their role in performance outcome motivate examining the potential role of SCM practices (a set of five SCM practices that are logically related between them) on organizational performance to better understand their value and relevance to the organization operating amid increased uncertainty and volatility in a dynamic and complex environment (Islami, 2021).…”
Section: The Mediating Role Of Scm Practicesmentioning
confidence: 99%
“…Quality management is one of the most well-accepted operations strategies to attain competitive advantages in the operations of companies along with retail sector (Agrawal, 2020; Zhang et al , 2019; García-Bernal and Ramírez-Alesón, 2015; Baird et al , 2011; Kaynak and Hartley, 2008), whereas the internal supply chains are limited to increase the operational efficiency of the firm (Choi et al , 2018; Walker et al , 2008). Literature highlights the high-level inter-relationship between quality and supply chain performance (Sharma and Modgil, 2019; Duong et al , 2019; Reddy et al , 2019; Marinagi et al , 2015). The global business trends influence SC-QM practices and firm performance (Kuei et al , 2001), therefore firms are now focusing on internal process improvement to circumscribe the globalization of their quality strategy (Lin et al , 2013; Wiengarten et al , 2013; Li et al , 2011; Soltani et al , 2011).…”
Section: Introductionmentioning
confidence: 99%